Panganan Kasus Gagap Dewasa dengan Metode Fluency Shaping: Studi Kasus Tunggal - Jumiarti jumiarti; Quamilla Sazha Aathirah; Hestiana Ningtyas (22013) (Jurnal Terapi Wicara, 2024)
A stuttere’s ability to produce speech fluently indicates of the success of a stuttering intervention. There is still little research related to the transfer of fluency to everyday situations, which is the reason for this research.